A numerical model based on ALE formulation to predict crack propagation in sandwich structures - Marco Francesco Funari; Fabrizio Greco; Paolo Lonetti; Saverio Spadea (Fracture and Structural Integrity)
A numerical model to predict crack propagation phenomena in sandwich structures is proposed. The model incorporates shear deformable beams to simulate high performance external skins and a 2D elastic domain to model the internal core. Crack propagation is predicted in both core and external skin-to-core interfaces by means of a numerical strategy based on an Arbitrary Lagrangian–Eulerian (ALE) formulation. Debonding phenomena are simulated by weak based connections, in which moving interfacial elements with damage constitutive laws are able to reproduce the crack evolution. Crack growth in the core is analyzed through a moving mesh approach, where a proper fracture criterion and mesh refitting procedure are introduced to predict crack tip front direction and displacement. The moving mesh technique, combined with a multilayer formulation, ensures a significant reduction of the computational costs. The accuracy of the proposed approach is verified through comparisons with experimental and numerical results. Simulations in a dynamic framework are developed to identify the influence of inertial effects on debonding phenomena arising when different core typologies are employed. Crack propagation in the core of sandwich structures is also analyzed on the basis of fracture parameters experimentally determined on commercially available foams.